Regulation of the immune microenvironment and immunotherapy after liver transplantation - Lan, Tianyi; Wu, Gang; Zuo, Bangyou; Yang, Jingming; He, Pan; Zhang, Yu (Frontiers in Immunology, 2025)
Liver transplantation (LT) is a primary treatment option for patients with end-stage liver disease. However, post-transplantation immune regulation is critical to graft survival and long-term patient outcomes. Following liver transplantation, the recipient’s immune system mounts a response against the graft, while the graft promotes anti-rejection immune reactions and the establishment of immune tolerance. In recent years, advances in the study of the immune microenvironment have provided new insights into post-transplantation immune regulation. Meanwhile, immunotherapy strategies have opened new possibilities for improving transplantation success rates and long-term survival. This review summarizes recent progress in understanding the immune microenvironment and immunotherapy following liver transplantation, focusing on key components of the transplant immune microenvironment, their regulatory networks and mechanisms, major immunosuppressive strategies, emerging immunotherapeutic approaches, and current challenges. The aim was to provide a theoretical foundation for optimizing clinical practice.